ESTIMATIONS OF LOCAL MAGNETIC FIELDS IN SOLAR FLARES: BASIC METHODS AND SOME RESULTS - Lozitsky, V. G.; Baranovsky, E. A.; Lozitska, N. I.; Tarashchuk, V. P. (Одеські астрономічні публікації, 2017)
We consider three methods for estimations of local magnetic fields in solar flares: (1) analysis of bisectors of I ± V profiles (Lozitsky, 2015); (2) search for Zeeman-like effects in cores of spectral lines with very low Lande factors, geff ≈ 0.01 (Lozitsky, 1993, 1998); (3) semi-empirical modeling using many spectral lines and two-component models (see, e.g., Lozitsky et al., 2000). We illustrate the application of named methods to different observational data and to different spectral lines. Our main conclusions are following: (a) upper limit of local magnetic fields in solar flares is, at least, ~104 G, (b) such extremely strong fields can occur in very small, spatially unresolved scales, (c) lifetime of such fields is, at least, a few minutes.